ショウワ キチ オキ ニ ケイセイ サレル エンガン ポリニア ノ スイオン コウゾウ - 牛尾, 収輝; ウシオ, シュウキ; 瀧澤, 隆俊; タキザワ, タカトシ; 大島, 慶一郎; オオシマ, ケイイチロウ; 河村, 俊行; カワムラ, トシユキ; Ushio, Shuki; Takizawa, Takatoshi; Ohshima, Kay I.; Kawamura, Toshiyuki (1993)
P(論文) 南極リュツォ・ホルム湾の定着氷域と沖合流氷域の間に形成される開水面領域において, AXBT(航空機投下式海水温水深計)を用いた海洋観測を行った。その結果, 結氷温度(-1.9～-1.8℃)でほぼ一様な水温を示す冬季対流混合層の深さが350～450mに達していた。これは沖合に広がる流氷域における混合層よりもかなり深い。また, 冬明けには混合層がやや深くなっている傾向も捕えられた。このような水温構造は, 大気・海洋に大きな影響を与える氷野内開水面の特徴と言える。 Open water areas between fast-ice and pack-ice zones are frequently observed off Lutzow-Holm Bay, Antarctica. In such open waters, called polynyas or leads, which are exposed to the cold air, new sea ice can form with a high growth rate. So the open polynya releases large quantities of heat to the atmosphere and excludes high-salinity brine to the ocean. In 1990-1992 the 31st and 32nd Japanese Antarctic Research Expeditions conducted oceanographic observations in Lutzow-Holm Bay to reveal the atmosphere-sea ice-ocean interaction. Thirty AXBT's (aircraft-deployed expendable bathythermograph) were cast to examine the thermal structure in the polynya "Otone Suiro". Based on the AXBT data the depths of the winter convective-mixed layer were estimated. The thickness of the mixed layer near the freezing point (-1.9～-1.8℃) reached to 350∿450m. These mixed layers were clearly thick as compared with those in the offshore pack-ice region. Furthermore the mixed layer has a tendency to deepen in winter. departmental bulletin paper